Initial productive performance of ‘Tahiti’ acid lime considering different rootstocks and levels of salt water - Oliveira Martins, Gabriel (Revista Ciência Agronômica, 2021)
The p roductive performance of citrus plants is limited by abiotic factors such as salinity. The response to these factors varies among rootstocks, and to guarantee sustainability of the production system, it is possible to identify the most suitable genotypes agronomically for each growing environment. Given the above, the aim of this study was to evaluate the productive performance of the ‘Tahiti’ acid lime combined with different citrus rootstocks irrigated with water at different levels of salinity during the fi rst year of fruit production. Three levels of electrical conductivity of the irrigation water (0.14, 2.40 and 4.80 dS m-1) and 13 rootstocks (‘Santa Cruz Rangpur’ lime, ‘Indio’, ‘Riverside’ and ‘San Diego’ citrandarins, ‘Sunki Tropical’ mandarin and eight hybrids generated by the Citrus Breeding Program of Embrapa Cassava & Fruits). The experimental design was of randomised blocks, with four replications and one plant per plot. The fruits were harvested from 300 to 720 days after transplanting (DAT) to pots with a capacity of 60 L, which had been adapted for use as lysimeters. Fruit production was determined by weight and number, in addition to measuring the size and the thickness of the peel. It was found that water of up to 2.4 dS m-1 can be used for citrus irrigation without signifi cantly compromising early fruit production in the ‘Tahiti’ acid lime when grafted on the ‘Sunki Tropical’ mandarin, ‘Riverside’ citrandarin, and on the hybrids TSKC x TRBK - 007, TSKC x CTTR - 012, HTR - 069, TSKC x (LCR x TR) - 040 and TSKC x (LCR x TR) - 059, which resulted in an earlier start to production. At the salinity level of 4.8 dS m-1, the ‘Tahiti’ acid lime proved to be more productive and less sensitive when grafted onto ‘Sunki Tropical’ mandarin, TSKC x TRBK - 007, TSKC x CTTR - 012, HTR - 069, and TSKC x (LCR x TR) - 040 hybrids.